Principal Leadership Strategy Management in Improving the Quality of Education Based on Iasp 2020 at MIN 2 Bandung City - Ahsyaf Muzakki; Mulyawan Safwandy Nugraha (al-Afkar, Journal For Islamic Studies, 2025)
This article is written to see the management of the principal's leadership strategy in improving the quality of education. The research method used in writing this article is a qualitative method with a descriptive approach. Data collection techniques are carried out through: first, in-depth interviews; second, participant observation and third, documentation. While the data collected through the three techniques above are then checked for validity by checking credibility. The results of the research on the type of principal leadership in improving the quality of education at MIN 2 Bandung City use namely by prioritizing cooperation in implementing leadership. The factors that influence efforts to improve the quality of education at MIN 2 Bandung City so that it becomes a superior school that is a favorite of the community are: 1) Principal Factor. 2) Teacher Factor 3) Student Factor 4) Resources Factor. The efforts of the head of MIN 2 Bandung City in improving the quality of education are: in addition to improving human resources, the head of MIN 2 Bandung City also increases various activities that involve all supporting elements in the school he leads.